(untitled) (The Review of Diabetic Studies, 2025)
Background: This study aimed to assess the long-term outcomes of liver transplantation (LT) for the treatment of hepatocellular carcinoma (HCC) according to the Milan Criteria (MC) in a university hospital. Methods: A cohort study of 100 HCC patients transplanted between 2006 and 2020. Patients were grouped according to MC for survival analysis, based on explant findings. The median follow-up duration was 65 months. Results: Perioperative mortality and recurrence rates were 5% and 9.5%, respectively. Recurrence appears within two years post-LT, and the median time until death was seven months (range 2-38). In univariate analysis, recurrence was more likely in the presence of Hepatitis B Virus (HBV), maximal tumor diameter > 50 mm, total tumor diameter > 70 mm, microvascular invasion, poor histological differentiation, and HCC stage beyond MC. The median alpha-fetoprotein (AFP) level and locoregional therapies (LRT) before LT showed no significant differences in recurrence rates. On multivariate analysis, factors associated with the recurrence rate were maximal tumor diameter > 50 mm, total tumor diameter > 70 mm, presence of microvascular invasion, and poorly differentiated tumors. The 5-year Overall Survival (OS) was 73.2% [95%CI 62.9-81]. According to explant biopsies, 70 patients were within MC (WMC) and 25 beyond MC (BMC), with significant differences in recurrence rates (2.8% vs. 28%, p<0.05) and 5-year OS rates (78.5% vs. 55.7%, p=0.0091). Conclusion: In our center, the 5-year OS rate for LT in HCC is over 70%, with a recurrence rate of 9.5%. Significant differences were found between the patients with and without MC.